Impact of the burden of caregivers of children with ASD on oral health - Beatriz Bueno FALQUETTI; João Victor Soares RODRIGUES; Amanda PAINO-SANT'ANA; Mariella Boaretti DEROIDE; Gabriel MULINARI-SANTOS; Letícia Helena THEODORO (Universidade Estadual Paulista, 2023)
Abstract Introduction the caregiver's demand to meet the needs of individuals with autism spectrum disorder (ASD) can influence their quality of life. Objective the objective of the present study was to compare the burden on caregivers of individuals with ASD with individuals neurotypical (N) and to evaluate the correlation of the impact of oral health with the burden on these caregivers. Material and method participants were divided into two groups: ASD Group (ASD; n=35) and Neurotypical Group (N; n=35). A sociodemographic characteristics questionnaire was administered to caregivers. Caregiver burden was measured using the Burden Interview (BI) questionnaire. The visible plaque index (VPI) of children was analyzed. The data were submitted to statistical analysis (α=5%). Result in the group ASD, the majority of participants were partially dependent, with the majority being dependent on oral hygiene. In group N, the majority were independent and self-sufficient in oral hygiene. Half of the caregivers in the group ASD felt mild to moderate burden (54.3%), while in group N it was found that more than half of them had no burden (65.7%). In the comparative analysis of data from the BI questionnaire, significant differences were observed between the groups in questions (p <0.001), which are directly related to childcare. Regarding the VPI of children in the group ASD and N groups compared to the level of burden, it was observed that there were no significant differences between the groups. Conclusion ASD caregivers have a greater burden when compared to N caregivers and the degree of burden did not influence the oral hygiene of the child with ASD.